Carbon dynamics in the future forest: the importance of long‐term successional legacy and climate–fire interactions. (11th September 2013) - Loudermilk, E. Louise; Scheller, Robert M.; Weisberg, Peter J.; Yang, Jian; Dilts, Thomas E.; Karam, Sarah L.; Skinner, Carl
Abstract Understanding how climate change may influence forest carbon (C) budgets requires knowledge of forest growth relationships with regional climate, long‐term forest succession, and past and future disturbances, such as wildfires and timber harvesting events. We used a landscape‐scale model of forest succession, wildfire, and C dynamics (LANDIS‐II) to evaluate the effects of a changing climate (A2 and B1 IPCC emissions; Geophysical Fluid Dynamics Laboratory General Circulation Models) on total forest C, tree species composition, and wildfire dynamics in the Lake Tahoe Basin, California, and Nevada. The independent effects of temperature and precipitation were assessed within and among climate models. Results highlight the importance of modeling forest succession and stand development processes at the landscape scale for understanding the C cycle. Due primarily to landscape legacy effects of historic logging of the Comstock Era in the late 1880s, C sequestration may continue throughout the current century, and the forest will remain a C sink (Net Ecosystem Carbon Balance > 0), regardless of climate regime. Climate change caused increases in temperatures limited simulated C sequestration potential because of augmented fire activity and reduced establishment ability of subalpine and upper montane trees. Higher temperatures influenced forest response more than reduced precipitation. As the forest reached its potential steady state, the forest could become C neutral or a C source, and climate change could accelerate this transition. The future of forest ecosystem C cycling in many forested systems worldwide may depend more on major disturbances and landscape legacies related to land use than on projected climate change alone.